Glycemic control and denture hygiene behaviors influence fungal colonization in older adult diabetic patients - Tanjapatkul, Chutikorn; Channarong, Montira; Kaewchutima, Narisara; Zakariah, Siti Zulaikha; Precha, Nopadol (KeAi Communications, 2025)
Objective: Denture-associated infections are common among older adult diabetic patients, particularly those with poor glycemic control. Chronic hyperglycemia promotes fungal adhesion, biofilm formation, and impaired oral immunity, while few studies have investigated how blood glucose levels and hygiene behaviors jointly influence microbial colonization on dentures. This study aimed to investigate the association between glycemic control, denture hygiene behaviors, and fungal colonization among older adult diabetic denture wearers in Nakhon Si Thammarat, Thailand. Methods: In this cross-sectional study of 80 diabetic denture wearers, we stratified participants by HbA1c status (≤ 7.0 % vs > 7.0 %) and quantified denture fungal burden alongside hygiene practices. Denture swabs were cultured on Sabouraud dextrose agar for quantitative fungal enumeration and species identification using VITEK MS PRIME. Results: Patients with poor glycemic control exhibited significantly higher fungal loads (P < 0.001). HbA1c emerged as the independent predictor in multiple regression analysis (β = 0.35, P = 0.041). Species level profiling revealed Candida albicans as dominant in uncontrolled patients followed by C. glabrata, C. tropicalis, Trichosporon asahii, and C. nivariensis. Conversely, C. dubliniensis and C. pelliculosa were uniquely identified in patients with good glycemic control. Hygiene practices revealed that brushing combined with chemical cleansing significantly reduced fungal concentration compared with rinsing with water alone (P = 0.013). Participants who cleaned their dentures after every meal also exhibited significantly lower fungal counts than those who cleaned only once daily (P = 0.05). Conclusion: Poor glycemic control is strongly associated with denture mycobiome dysbiosis and increased fungal diversity in diabetic patients. The findings underscore HbA1c as a potential microbial risk indicator and emphasize the need for integrated diabetes management and targeted oral hygiene interventions to prevent denture-related fungal infections among older adults.